The Philosophy of Social Life in the ‘Ayniyah’ of Abu Dhu’aib al-Hudhali - Mohammed , Dr. Ammar Hazem (Thi Qar Arts Journal, 2024)
“The manifestations of living and the philosophy of daily life, which are dispersed throughout the odes of Abu Dhu’aib al-Hudhali, represent a model that reflects the philosophy of social life and the general vision that can reveal the poet’s philosophy in dealing with all the details of the material and spiritual life of the pre-Islamic era. This life was associated with everything that can be found in the description of death and life, and the relationship with both the silent and active nature, as well as the geography that forms a space carrying all the cultural connotations presented by it as an icon that can emulate what the pre-Islamic poet feels and his vision of the Bedouin world and its values.”